Keanekaragaman dan komposisi jenis plankton pada kolam bioflok ikan nila (Oreochromis niloticus) - Ni Kadek Vindi Wedhawati; Pande Gde Sasmita Julyantoro; Dewa Ayu Angga Pebriani (Bumi Lestari Journal of Environment, 2022)
Aquaculture is an activity to cultivate aquatic biota in controlled media. One of the cultivated fish resources is tilapia (Oreochromis niloticus). Tilapia production continues to be increasing to meet increasing of consumer demand. The emergence of the problem of organic matter levels in the water could be harmful to both of fish and the environment. One of the solution to overcome this problem is by application of biofloc technology. The purpose of this study was to determine the diversity and composition of plankton species in tilapia biofloc ponds in Tiga Village, Susut District, Bangli Regency. This research was conducted in March-May 2021 in Tilapia Biofloc Pond. The research used a simple random sampling method. Sampling was carried out once in three biofloc ponds where each pond had 5 points. Data analysis is using the Microsoft Excel program. The data is present in the tables and charts consisting of the abundance, diversity, composition, dominance, and uniformity index of plankton. Based on the research results, it is known that there are 12 genus of phytoplankton and 4 genus of zooplankton. Phytoplankton diversity index values ??ranged from 1.31 to 1.65. Zooplankton diversity index values ranged from 0.79 to 1.08. The composition of phytoplankton species came from the genus Scenedesmus, Chlorella, Coelastrum, Chroococcus, Gonatozygon, Pediastrum, Nitzschia, Navicula, Synedra, Triceratium, Chaetoceros, and Pesudanabaena. The composition of zooplankton species comes from the genus Brachionus, Euchlanis, Tokophyra, and Vorticella. The water quality measured during the study was a temperature value ranging 25 oC, a pH value ranging from 7,12 – 7,18, a DO value ranging from 6.6 to 6.9 mg/L, an ammonia value ranging from 1.41 to 1.51 mg/L, and a nitrate value ranging from 1.84. -3.69 mg/L. This value is still in the optimal range for plankton life.